EVALUASI RUTE DISTRIBUSI PRODUK NESTLE MENGGUNAKAN METODE SAVING MATRIX DAN NEAREST NEIGHBOR PADA UD ANDATU MULIA KABUPATEN JEMBER - Widayati, Amrih; Gusminto, Eka Bambang; Awwaliyah, Intan Nurul; Maridelana, Vanya Pinkan (Jurusan Manajemen Fakultas Ekonomi dan Bisnis, 2024)
PT NestlÃ© Indonesia is one of the leading and well-known food and beverage producers in Indonesia. This study aims to evaluate the distribution route used by one of PT NestlÃ© Indonesia's authorized distributors, UD Andatu Mulia, which operates in Jember Regency. The data analysis methods employed are the Saving Matrix and Nearest Neighbor methods. The data includes demand quantities, distances between stores, and the amount and capacity of available transportation. The results indicate that the use of the Saving Matrix and Nearest Neighbor methods can generate four optimized distribution routes, resulting in a distance savings of 173.84 km, or 24%. Additionally, the total savings in shipping costs calculated using these methods amounts to Rp1,380,593 per day or Rp33,134,235 per month, representing a 22% reduction in costs. This research offers practical implications and can serve as a reference for UD Andatu Mulia in determining optimal distribution routes to minimize shipping costs and optimize delivery times to customers.